Renewable energy forecasting : from models to applications - Kariniotakis, Georges (Woodhead Publishing in energy., 2017)
This book provides an overview of the state-of-the-art of renewable energy forecasting technology and its applications. After an introduction to the principles of meteorology and renewable energy generation, groups of chapters address forecasting models, very short-term forecasting, forecasting of extremes, and longer term forecasting.